The hero, the rival, and the dragon: the tripartite structure of Kallimachos and Chrysorrhoe - Fonseca, Rui Carlos (2017)
This article focuses on the narrative structure of the Byzantine vernacular romance Kallimachos and Chrysorrhoe. I argue that the first half of the romance is built upon a tripartite pattern, telling the stories of three male characters playing the role of the princess’ suitor. These three male characters are the hero, the rival, and the dragon, and their stories are reshaped and adapted from a common basic plot, each involving a similar set of typical situations and repeated motives.